2020
DOI: 10.1108/shr-05-2020-0049
|View full text |Cite
|
Sign up to set email alerts
|

Employee age and the impact on work engagement

Abstract: Purpose Employee engagement studies are popular in contemporary research because of the complexity organizations face in nurturing the performance and productivity of multi-generations of workers. The purpose of this paper is to assess association of age and dimensions of work engagement. Design/methodology/approach In total, 181 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 10 publications
4
26
1
4
Order By: Relevance
“…Previous studies have identified variables associated with work engagement and/or intention to quit. These variables are age [88][89][90], gender [88,90,91], marital status [88,90], and parental status [92]. Moreover, we controlled for the stress related to the COVID-19 pandemic since data were collected during the pandemic and previous studies found that stress was associated with job performance [41].…”
Section: Control Variablesmentioning
confidence: 99%
“…Previous studies have identified variables associated with work engagement and/or intention to quit. These variables are age [88][89][90], gender [88,90,91], marital status [88,90], and parental status [92]. Moreover, we controlled for the stress related to the COVID-19 pandemic since data were collected during the pandemic and previous studies found that stress was associated with job performance [41].…”
Section: Control Variablesmentioning
confidence: 99%
“…Job satisfaction affects work engagement [44]. Further, although age, sex, educational background, marital status, and number of children have not been consistently studied in previous studies [45][46][47], they have been shown to affect work engagement and have been used as control variables.…”
Section: Introductionmentioning
confidence: 99%
“…The significant variables were categorized according to (1) year of survey; (2) region of hospital; (3) gender; (4) age group; (5) years of employment; (6) physician status; (7) specialty; and (8) job position. Multivariate analysis using linear regression analysis was performed to identify and adjust for a range of covariates, including the significant variables from Table 1 , which are the factors associated with physician engagement obtained from the literature review, including hospital region, gender, age, years of employment, physician status, and job position [ 26 , 27 , 28 , 29 ]. Missing data were removed to avoid any bias in analyzing the results.…”
Section: Methodsmentioning
confidence: 99%